Land Utilisation in Arid Zones of Gujarat- Problems and Potentials - Sharma, R.C. (Journal of Soil and Water Conservation, 2022)
Nearly 51 per cent of area in Gujarat falls under arid and semi-arid climatic zones. The arid plain of Kacchh is undulating sandy waste lands without drainage lines. Acacia sp. and coarse grasses on the hills and jowar, bajra, cotton and wheat on flat ridges and inter-hilly basin form the characteristic land use of the region. The semi-arid plains of Gujarat traversed with river Matti, Sabarmati and Banas are intensively cultivated for tobacco, cotton, banana, sugarcane, wheat, fur, potato and mango orchards. The soils are deep, loamy sand to loam, well drained and fairly moisture retentive with low to medium fertility. The semi-arid basaltic landscape of Saurashtra have undulating and hilly terrain. The region is rich in surface and ground water potentials and a number of small dams have been constructed on shallow and rocky river beds. It is a multicrop region. Shallow soils, erratic rainfall and soil erosion are the major problems. The area with concave topography exhibits salinity problem. Improved water harvesting techniques from the porous catchments, use of saline waters amid some suitable farming techniques for better soil and water conservation have been discussed. Use of remote sensing in generating data needed for planning and monitoring the development of such regions in a time and cost effective manner is also highlighted.